ANALISIS PENDEKATAN SAINTIFIK MELALUI MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS VII PADA MATERI HIMPUNAN - Ayu Rekno Kusuma Dewi; Aflich Yusnita Fitrianna; M. Afrilianto (IKIP Siliwangi, 2023)
This study aims to analyze the effect of the scientific approach through the discovery learning modelon students' mathematical understanding abilities. This research is a classroom action research. This research was conducted on 17 students of class VII at one of the junior high schools around Bandung district for the academic year 2021/2022. The material used is the set material. The test instrument used is a mathematical understanding ability test as many as 6 items in the form of a description of the set material. The non-test instrument used was a questionnaire on the attitude scale of students' interest in learning mathematics with 10 positive and negative statement scales. This research has a conducted in two cycles, the first cycle consisting of two meetings and the second consisting of two meetings with in the end carried out pre-test and post-test activities. Student learning outcomes in this study obtained N-Gain data in the Average category with a score of 0.76 and concluded that the application of the scientific approach through the discovery learning model had an effect on students' mathematical understanding abilities with student learning interest of 75%.